Recommendations for reporting results of diagnostic genetic testing (biochemical, cytogenetic and molecular genetic) - Claustres, Mireille; Kožich, Viktor; Dequeker, Els; Fowler, Brain; Hehir-Kwa, Jayne Y; Miller, Konstantin; Oosterwijk, Cor; Peterlin, Borut; van Ravenswaaij-Arts, Conny; Zimmermann, Uwe; Zuffardi, Orsetta; Hastings, Ros J; et al. (European journal of human genetics, 2014)
Genetic test results can have considerable importance for patients, their parents and more remote family members. Clinical therapy and surveillance, reproductive decisions and genetic diagnostics in family members, including prenatal diagnosis, are based on these results. The genetic test report should therefore provide a clear, concise, accurate, fully interpretative and authoritative answer to the clinical question. The need for harmonizing reporting practice of genetic tests has been recognised by the External Quality Assessment (EQA), providers and laboratories. The ESHG Genetic Services Quality Committee has produced reporting guidelines for the genetic disciplines (biochemical, cytogenetic and molecular genetic). These guidelines give assistance on report content, including the interpretation of results. Selected examples of genetic test reports for all three disciplines are provided in an annexe.
Keywords: zajištění kvality zdravotní péče; genetické testování; zveřejnění; Prenatal Diagnosis; Disclosure; Quality Assurance, Health Care; Humans; prenatální diagnóza; Genetic Testing; genetické poradenství; Molecular Diagnostic Techniques; cytogenetické vyšetření; diagnostické techniky molekulární; Genetic Counseling; lidé; Cytogenetic Analysis